The use of mentoring for knowledge translation by allied health: a scoping review. Issue 4 (14th December 2022) - Howlett, Owen; O'Brien, Chris; Gardner, Marcus; Neilson, Cheryl
ABSTRACT: Objective: To describe how allied health professionals have used mentoring as a knowledge translation strategy to inform practice. Introduction: Mentoring has been reported to be used by nursing and medicine as a knowledge translation strategy. It is not known if allied health professionals have also used mentoring to improve their use of research in practice, or what the key mentoring characteristics are that guide its application in allied health settings. Improved understanding of the barriers and facilitators to mentoring in allied health settings may be used to guide the design of future mentoring programs to assist knowledge translation. Inclusion criteria: Eligible studies must have included allied health professionals, and used the concept of mentoring to support knowledge translation in the context of healthcare. Primary empirical and synthesized studies were eligible. Methods: An a-priori protocol was followed to complete a search of six databases (MEDLINE [OVID], EMBASE [OVID], CINAHL [EBSCO], PsycInfo [OVID], PDQ-Evidence (www.pdq-evidence.org ), and Cochrane on the 9 March 2021. Screening for eligibility was conducted by two authors at the title and abstract stage and the full text stage. Selection criteria and the data extraction tool were established prior to the search. Findings are presented in narrative and tabular formats. Results: A total of 2053 studies met the inclusion criteria for screening and nine were determined to be eligible for inclusion. Mentoring has been used by allied health professionals to improve the translation of interventional research evidence by clinicians, and to establish clinician skills and knowledge relating to knowledge translation processes. Mentoring was predominantly used as part of a multifaceted knowledge translation strategy alongside educational strategies. Mentoring characteristics such as structure, context, goals, resourcing and dosage varied depending on the context of translation. The specific barriers reported to using mentoring were varied, whereas the facilitators to mentoring were primarily related to the mentor's approach and expertise. The impact of mentoring was primarily measured through the mentee's experience of mentoring. Conclusions: Allied health professionals have used mentoring as a knowledge translation strategy to enhance the use of research evidence in their practice and to learn the process of knowledge translation. Mentoring is mostly used in conjunction with other strategies in practice, such as education. The limited number of identified barriers and facilitators to using mentoring as a knowledge translation strategy supports the need for future research to deepen our understanding about the mentoring process.